Energy Transition and Green Welfare State: Reimagining Energy Legal Politics within the Framework of Welfare and Sustainability - Aji Baskoro (UIN Sunan Kalijaga Yogyakarta, 2025)
The global climate crisis and the imperative of sustainable development have positioned energy transition as a crucial agenda. In the Indonesian context, despite the constitutional mandate towards a welfare state, the implementation of energy transition policies has not fully reflected these principles. This study aims to analyze the energy law politics of energy transition in Indonesia from the perspective of the welfare state and to explore the potential of the green welfare state as a more comprehensive alternative framework. The research methodology employed is a normative legal study with statutory and conceptual approaches. Data were collected through the analysis of relevant legislation and literature, which were subsequently analyzed qualitatively using content analysis. The research findings indicate that the current implementation of energy transition policies still faces significant challenges in realizing equitable energy access, the protection of vulnerable groups, meaningful public participation, and the proactive role of the state in regulation and oversight. This study concludes that the green welfare state framework, underpinned by the philosophy of ecocentrism and intergenerational justice, and integrating social and ecological justice, offers a more holistic approach to reformulating just and sustainable energy law politics in Indonesia. The implementation of this framework necessitates a strong state commitment, inclusive participation from all stakeholders, and the establishment of regulations that support a just and environmentally friendly transition.